Effect of different dietary nitrogen sources on growth performance of crossbred cattle - Lailer, P C; Singh, G P (The Indian Journal of Animal Sciences, 2012)
Male crossbred calves (20) were randomly divided into 4 groups of 5 each and fed groundnut-cake (T1). cottonseed-cake (T2), mustard-cake ((T3) and urea-based concentrate rations ((T4)) and wheat straw. Growth rate was significantly (P0 05) and N balances were 19.00; 23.43: 16.67; and 18.58 g/day in the respectivc groups. From the growth performance and N-balance data it could be concluded that different dietary-N sources can be replaced by each other without adverse effect. However, the cost of feeding as well as cost per kg gain was lower on urea-based ration.